Studi Eksprimental Pengaruh Kinerja Pompa Sentrifugal Seri Dan Paralel Menggunakan Fluida Crude Palm Oil (Non Newtonian) - Yus Randi Adhari F; Amnur Akhyan (Politeknik Caltex Riau, 2022)
This test is to see the performance of the pump in series and parallel installation using a centrifugal booster pump to drain Crude Palm Oil. The fluid flow is monitored by a pressure gauge as a pressure detector and a flowmeter as a flow meter to detect Crude Palm Oil’s flow. Has a reservoir with a volume of 45 liters, and uses a 1 inch galvanized pipe. The largest pressure value is obtained by a series pump circuit, of 6 Psi. While the lowest pressure value is obtained by a parallel pump circuit, which is 3 Psi. At a temperature of 80°C, the largest flow rate produced by a parallel circuit is 60 lpm, while the smallest discharge is produced by a series pump circuit of 32 lpm. Meanwhile, at room temperature, the parallel circuit flow rate was recorded at 17 lpm, and the series pump circuit as much as 12 lpm. The pump with the best efficiency with a series circuit is 97%, while in a parallel pump circuit it is 89%.